DIAGNOSTIC SIGNIFICANCE OF IMMUNITY MARKERS IN INFLAMMATORY CARDIOMYOPATHY PATIENTS - S. N. Tereschenko; A. A. Skvortsov; A. Yu. Schedrina; O. Yu. Narusov; K. A. Zykov; A. A. Safiullina; A. V. Sychev; I. V. Zhirov (Российский кардиологический журнал)
Aim. To evaluate diagnostic significance of biomarkers for inflammatory cardiomyopathy (ICM).Material and methods. Totally, 35 patients included with suspected inflammatory cardiomyopathy, chronic heart failure of I-III functional class (FC), decreased systolic function of the left ventricle (EF LV <40%). All patients, together with routine assessments, underwent endomyocardial biopsy (EMB). Studying bioptates, the methods were used of histology and immunohistochemistry with monoclonal antibodies to monocytes/macrophages, to T-lymphocytes (CD 45RO, CD3+, CD4+, CD8+, CD68+).Diagnosis of ICM was set if in myocardium there were inflammatory infiltrates related to degeneration or necrosis of myocytes of non-ischemic origin, and number of leucocytes was 14 or more (including up to 4 monocytes) in 1 mm2 of specimen, and at least 7 of them should be CD3+ T-lymphocytes. According to the results, patients were selected to the groups of ICM and non-inflammatory dilation ardiomyopathy (niDCM). In all patients we evaluated the following biomarkers: immunoglobulines A, M, G, high-sensitive C-reactive protein (hsCRP), matrix metalloprotease-9 (MMP9), transforming growth factor β (TGFβ), tumor necrosis factor α, (TNFα), C3 and C4 components of complement, eosinophilic catione protein (ECP).Results. While comparing groups ICM and niDCM by the parameters of humoral immunity, it was revealed that levels of hsCRP, C3 and C4 complement, MMP9, TGFβ were significantly higher in ICM group. In ROC analysis it was found that only hsCRP, C3 and C4 complement and MMP9 have diagnostic significance. The levels of the biomarkers mentioned, were assessed with a threshold definition for optimum sensitivity and specificity: 1,13 mg/mL, 1,2 g/L, 0,256 g/L, 680 ng/mL, respectively. Using combined biomarkers hsCRP with C3, C4 complement sensitivity reached 61%, specificity 94%; in MMP6 with C3, C4 complement — 66% and 94%, respectively.Conclusion. Combination of hsCRP and MMP9 with C3, C4 components of complement is worthy to use in diagnostics of ICM.